Causas de las controversias tributarias sobre exoneración del impuesto general a las ventas en las empresas Avícolas S.A.C. de Tarapoto. Periodo 2007 - 2011 - Bardales Cárdenas, Héctor (2013)
The purpose of this thesis is to "Determine the causes of the above tax exemption contained in Appendix 1 (property) of the General Sales Tax, through surveys in order to propose reasonable application of the objectives of the standard regarding the accounting principies applied Equity and Relevance in the Poultry business operations Tarapoto SAC. Period 2007-2011. The core problem is formulated as follows: What are the causes of disputes over tax exemption of the General Sales Tax contained in Appendix 1 (assets) in companies Tarapoto Pouftry SAC. Period 2007-2011? The hypothesis is: The causes of disputes is due to poor interpretation and / or implementation of the objectives of the Act tax exemption tax on Appendix 1 (assets) and the accounting principles applied Equity and Relevance in commercial transactions SAC poultry companies Tarapoto. The methodology is based on the selection of the sample in SAC poultry companies Tarapoto. For the testing of the hypothesis was applied transactional descriptive non experimental design, applying the analytic-synthetic methods and the inductive-deductive. Applied research is a descriptive contrasting. The hypothesis is related to the problem and objetives.